Sphingosine‐1‐phosphate as a key player of insulin secretion induced by high‐density lipoprotein treatment. Issue 6 (26th March 2021) - Brulhart‐Meynet, Marie‐Claude; Thomas, Aurélien; Sidibé, Jonathan; Visentin, Florian; Dusaulcy, Rodolphe; Schwitzgebel, Valérie; Pataky, Zoltan; Philippe, Jacques; Vuilleumier, Nicolas; James, Richard W.; Gosmain, Yvan; Frias, Miguel A.
Abstract: Beta cell failure is one of the most important features of type 2 diabetes mellitus (T2DM). High‐density lipoprotein (HDL) has been proposed to improve β‐cell function. However, the mechanisms involved in this process are still poorly understood. The aim of this study was to investigate the contribution of sphingosine‐1‐phosphate (S1P) in the impact of HDL treatment on insulin secretion by pancreatic β‐cells and to determine its mechanisms. Primary cultures of β‐cells isolated from rat were treated with or without HDL in the presence or absence of S1P pathway inhibitors and insulin secretion response was analyzed. The S1P content of HDL (HDL‐S1P) isolated from T2DM patients was analyzed and correlated to the HDL‐induced insulin secretion. The expression of genes involved in the biosynthesis of the insulin was also evaluated. HDL as well as S1P treatment enhanced glucose‐stimulated insulin secretion (GSIS). In HDL isolated from T2DM patients, while HDL‐S1P was strongly correlated to its pro‐secretory capacity ( r = 0.633, p = 0.005), HDL‐cholesterol and apolipoprotein AI levels were not. HDL‐induced GSIS was blocked by the S1P1/3 antagonist but not by the S1P2 antagonist, and was also accompanied by increased intracellular S1P in β‐cells. We also observed that HDL improved GSIS without significant changes in expression levels of insulin biosynthesis genes. Our present study highlights the importance HDL‐S1P in GSIS in T2DM patients and demonstrates that HDL induces insulin secretion by a process involving both intra‐ and extra‐cellular sources of S1P independently of an effect on insulin biosynthesis genes. Abstract : HDL improves insulin secretion by beta cells S1P plays a role in HDL‐induced insulin secretion HDL increases intracellular S1P content.